Pro Active Record Databases with Ruby and Rails - Pytel, Chad; Yurek, Jonathan; Marshall, Kevin (Apress : Imprint: Apress, 2007)
Pro Active Record helps you take advantage of the full power of your database engine from within your Ruby programs and Rails applications. ActiveRecord, part of the magic that makes the Rails framework so powerful and easy to use, is the model element of the Rails Model-View-Controller framework. It's an object-relational mapping library enabling you to interact with databases from both Ruby and Rails applications. Because ActiveRecord is configured with default assumptions that mesh perfectly with the Rails framework, Rails developers often find they hardly need think about it at all. However, if you are developing in Ruby without Rails, or are deploying against legacy databases designed without Rails in mind, or you just want to take advantage of database-specific features such as large objects and stored procedures, you need the in-depth knowledge of ActiveRecord found in this book. In Pro Active Record, authors Kevin Marshall, Chad Pytel, and Jon Yurek walk you through every step from the basics of getting and installing the ActiveRecord library to working with legacy schema to using features specific to each of todays most popular database engines, including Oracle, MS SQL, MySQL, and more! You'll come to a deep understanding of ActiveRecord that will enable you to truly exploit all that Ruby, Rails, and your chosen database platform have to offer.